Democratic Republic of Sao Tome and Principe : Fifth Review Under the Three-Year Arrangement under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2008)
Economic activity continues to be robust in 2007, driven by foreign investment in tourism-related construction and services. The central bank (BCSTP) strengthened its efforts to control liquidity growth. Progress on structural reforms has been mixed. The authorities intend to accelerate public financial management reform. The authorities and IMF staff shared the view that the country's fiscal and external financing strategies need to adjust to the uncertain oil revenue prospects. The BCSTP is committed to deepening foreign exchange market reform.